2015
DOI: 10.1371/journal.pone.0133552
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-Associated Macrophages Provide Significant Prognostic Information in Urothelial Bladder Cancer

Abstract: Inflammation is an important feature of carcinogenesis. Tumor-associated macrophages (TAMs) can be associated with either poor or improved prognosis, depending on their properties and polarization. Current knowledge of the prognostic significance of TAMs in bladder cancer is limited and was investigated in this study. We analyzed 184 urothelial bladder cancer patients undergoing transurethral resection of a bladder tumor or radical cystectomy. CD68 (pan-macrophage marker), MAC387 (polarized towards type 1 macr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
48
1
5

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 29 publications
9
48
1
5
Order By: Relevance
“…Aside from the IL‐10‐ and PD‐L1‐mediated effects presented in this study, we think that other immunosuppressive mechanisms are present in bladder cancer patients to suppress their antitumour immunity. Following surgical resection, bladder cancer patients who had higher TAM density presented higher risk of tumour recurrence and shorter disease‐free intervals (Ajili et al, ; Bostrom et al, ), which cannot be explained by the direct, tumour cell‐mediated mechanism presented here because the tumour mass was not present. Therefore, further investigations are required for full understanding of the immune regulation in bladder cancer.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Aside from the IL‐10‐ and PD‐L1‐mediated effects presented in this study, we think that other immunosuppressive mechanisms are present in bladder cancer patients to suppress their antitumour immunity. Following surgical resection, bladder cancer patients who had higher TAM density presented higher risk of tumour recurrence and shorter disease‐free intervals (Ajili et al, ; Bostrom et al, ), which cannot be explained by the direct, tumour cell‐mediated mechanism presented here because the tumour mass was not present. Therefore, further investigations are required for full understanding of the immune regulation in bladder cancer.…”
Section: Discussionmentioning
confidence: 84%
“…TAMs could also support angiogenesis and increase tumour cell invasion and motility (Qian and Pollard, 2010). Higher density of CD68-expressing TAMs was associated with higher tumour grade and worse survival in bladder cancer patients (Bostrom et al, 2015), as well as poorer response to BCG therapy (Ayari et al, 2009). Importantly, TAMs in many tumours express high levels of the programmed death ligand 1 (PD-L1) (Noy and Pollard, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Horn et al (2015) showed that a high FOXP3/CD8 ratio within invasive cancer tissue was an independent predictor of poor overall survival after cystectomy [23]. High numbers of CD68+ TAMs were associated with an advanced pT category and high-grade cancer [24], acting as an additional independent factor (CD68/CD3 ratio > 1) with a more than 7-fold higher risk of cancer-specific death on multivariate analysis [25]. Conversely, increased intratumoral CD3+ and CD8+ T-cells were predictive of significantly better overall and disease-free survival [2627].…”
Section: Discussionmentioning
confidence: 99%
“…To assess the impact of macrophages on AMPKα, U937 cells which were differentiated with PMA to become macrophage-like cells were utilized because they express similar cell surface markers as the macrophages present in bladder cancer [33], [36], [46]. Treatment of human bladder cell lines with CM from U937 macrophages elicited downregulation of AMPKα1, AMPKα2, and the total AMPKα1/α2 at the protein level but not at the mRNA level.…”
Section: Discussionmentioning
confidence: 99%